Islamic Pedagogy on Human Resource Management based on Islamic References - Uzair Abbazi; Iace Ahmad Zarqan (Journal of Islamic Business and Economic Review, 2019)
In the Islamic perspective, spiritual and material progress are integrated. Islam also integrates individual and collective development. It is aiming to develop whole aspects simultaneously. No aspect of the human being is allowed to develop unduly or at the cost of others. It integrates its regulations of fair (Ad’l) and spiritual morality (Ihsaan and Taqwa). The principles of Islamic religion in term of human resource management are able to prove to be useful in dealing with the problems in an efficient ways which stem primarily from the HRM related challenges faced by the institutions or organizations. Application of Islamic HRM principles is able to help in solving crisis in training, leadership, essential professional skills, knowledge and attitudes required for productive careers and useful role in society. This paper will introduce a special issue on Islam and human resource management (HRM). Design/methodology/approach, The paper introduces a further current understanding of the relation between Islam and HRM based on the facts of history. The paper will also try to identify the key features of an Islamic HRM model that is substantially distinctive from existing models of HRM.